Pengaruh Asap Rokok Terhadap Histopatologi Koklea: Studi pada Tikus Putih (Rattus norvegicus) - Bambang Udji Djoko Rianto (MEDIA MEDIKA INDONESIANA, 2013)
ABSTRACT The effect of cigarette smoke on histopathology of cochleaBackground: Clinical studies have suggested that cigarette smoking associate with hearing loss. Smoke exposure is a risk factor to endothelial disfunction and developing atherosclerosis. Cochlea is a auditory organ that is sensitive to hipoxia condition. Objective this study was to determine the effect of cigarette smoke exposure to histological cochlear integrity.Methods: This was post test only design experimental study, using twenty male rats (Rattus norvegicus) were divided into 2 groups. The control group (10 rats) was kept in room free from cigarette smoke, while the experimental group (10 rats) was exposed to tobacco smoke, two cigarette per 1 hour exposure, twice a day, every work day, for 6 months from July 2004-February 2005. The cochlea rats were examined in Patologi Anatomi Laboratory Gadjah Mada University for histopathological examination.Results: There was 1 rat died in each group, and 18 rats (9 control group and 9 experimental group) were still alive. Based on histopathological result, there were abnormality in 7 rats (77.7%) of experimental group while all of control group were normal. This difference is significant statistically with Relatif Risk (RR) was 3.5 (95% CI: 0.66-34.53). The histopathological abnormality were of congestion of capilare, vacuolar degeneration, foam cell and necrosis of hair cells.Conclusion: Tobacco smoke causes histopatological abnormality in cochlear integrity. The relatif risk (RR) of histopathological abnormality on experimental group was 3.5.Keywords: Tobacco smoke, cochlea, stria vascularis, hair cells ABSTRAKLatar belakang: Beberapa studi klinik membuktikan bahwa kebiasaan merokok berhubungan dengan penurunan pendengaran. Paparan asap rokok merupakan faktor risiko terhadap disfungsi endotel yang dapat berkembang menjadi aterosklerosis. Koklea merupakan organ pendengaran yang sensitif terhadap keadaan hipoksia. Penelitian ini membuktikan pengaruh paparan asap rokok terhadap integritas histologis koklea.Metode: Rancang penelitian eksperimental yang digunakan adalah post test only design, dengan sampel sebanyak 20 ekor tikus putih jantan (Rattus norvegicus) dibagi menjadi 2 kelompok. Kelompok kontrol (10 ekor) disimpan di dalam ruangan bebas asap rokok. Kelompok eksperimental (10 ekor) diberi pajanan asap rokok 2 batang rokok per pajanan selama 1 jam, 2 kali sehari, setiap hari kerja selama 6 bulan dari bulan Juli 2004-Februari 2005. Koklea tikus diperiksa secara histopatologi di Laboratorium Patologi Anatomi Fakulatas Kedokteran Hewan Universitas Gadjah Mada.Hasil: Dari seluruh sampel didapatkan pada masing-masing kelompok 1 sampel mati, sedangkan 18 ekor tikus yang berhasil hidup sampai akhir masa pajanan (masing-masing kelompok 9 ekor) terdapat kelainan histologi pada 7 (77,7%) ekor tikus kelompok pajanan dengan RR 3,5 (95% CI: 0,66-34,53). Perubahan histopatolgi yang terjadi berupa kongesti pembuluh darah, degenerasi vakuoler, foam cell dan nekrosis sel rambut getar.Simpulan: Asap rokok berpengaruh pada kerusakan integritas histologis koklea. Kerusakan koklea pada kelompok pajanan asap rokok lebih besar dibanding kelompok kontrol dengan risiko relatif/RR sebesar 3,5.